A comparison of simultaneous and sequential visuo-spatial memory in children born very preterm. Issue 4 (19th May 2022) - Retzler, Jenny; Johnson, Samantha; Groom, Madeleine J.; Cragg, Lucy
ABSTRACT: Research suggests that children born very preterm (≤32 weeks' gestation) are at greater risk of impairments in information processing (particularly when information is presented simultaneously rather than sequentially) and visuo-spatial short-term and working memory relative to children born at term. This study compared the performance of children born very preterm with their term-born peers to elucidate the nature of group differences in these areas. 113 children (65 very preterm; 48 term-born) aged 8-to-11 years completed four visuo-spatial recall tasks. Tasks varied by presentation type (simultaneous or sequential) and memory type (short-term or working memory). Both groups recalled more locations in simultaneous than sequential tasks, and in short-term than working memory tasks. In short-term memory tasks, children born at term recalled more locations than children born very preterm for the sequential task, but groups did not differ on the simultaneous task. The opposite pattern was observed in the working memory tasks, with no group differences on the sequential task, but better performance on the simultaneous task for children born at term. Our findings indicate that simultaneous processing may not be impaired in children born very preterm per se, with poorer performance observed only under high cognitive demand. This interaction suggests very preterm birth may affect the level of cognitive resources available during feature integration, the consequences of which become apparent when resources are already stretched. The impact of interactions with cognitive demand in this population should be an important consideration for educational support strategies, and for assessment in research and clinic.